2014
DOI: 10.1103/physreva.90.033608
|View full text |Cite
|
Sign up to set email alerts
|

Composite pulses for interferometry in a thermal cold atom cloud

Abstract: Atom interferometric sensors and quantum information processors must maintain coherence while the evolving quantum wavefunction is split, transformed and recombined, but suffer from experimental inhomogeneities and uncertainties in the speeds and paths of these operations. Several error-correction techniques have been proposed to isolate the variable of interest. Here we apply composite pulse methods to velocity-sensitive Raman state manipulation in a freely-expanding thermal atom cloud. We compare several est… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 56 publications
(71 reference statements)
0
72
0
Order By: Relevance
“…Additionally, the increased Raman power enables one to reduce Rabifrequency inhomogeneity by increasing Raman beam waist, further improving pulse efficiency. Pulse efficiency can also be improved by using composite pulses [5,19,20].…”
Section: Interferometermentioning
confidence: 99%
“…Additionally, the increased Raman power enables one to reduce Rabifrequency inhomogeneity by increasing Raman beam waist, further improving pulse efficiency. Pulse efficiency can also be improved by using composite pulses [5,19,20].…”
Section: Interferometermentioning
confidence: 99%
“…In addition to the rectangular and Gaussian pulses, we discuss two other representative pulse shapes: (i) the GSinc pulse, which is the product of a Gaussian and a cardinal sine, and (ii) the Gaussian-Flat pulse (labeled GFlat thereafter) which is a flat pulse with Gaussian edges. For completeness of the presentation, we study in section 4 the influence of pulse shaping on the frequency selectivity, in line with previous works [26,27]. Finally, we present in section 5 a correction to the interferometer scale factor associated with pulse shaping, and discuss its relevance for different precision measurements involving AI based sensors.…”
Section: Introductionmentioning
confidence: 76%
“…Efficient transitions (i.e. high contrasts) can thus be achieved by temporally shaping the pulse intensity and phase, as shown in [26,27]. Moreover, when driving an interferometer with large momentum transfer (LMT) atom optics, it has been shown that pulses of Gaussian temporal shape significantly improve the transfer efficiency with respect to rectangular pulse shapes [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…We have explored the performance of several established NMR pulse sequences when applied to velocitysensitive Raman state manipulation in a freely expanding cold atom cloud, allowing the inversion infidelity to be halved [16]. The agreement between experimental measurements and simple predictions shows the underlying coherence of the atomic ensemble.…”
Section: Composite Pulse Techniques For Fidelity Enhancementmentioning
confidence: 99%